Daya Hambat Ekstrak Daun Kakao (Theobroma Cacao L.) terhadap Pertumbuhan Candida Albicans - Nadya Indah Permataningrum; Leni Rokhma Dewi; Ayu Mashartini Prihanti (Pustaka Kesehatan, 2019)
Candidiasis is an infection caused by overgrowth of Candida species in the oral cavity dominated by C. albicans. One way to inhibit the growth of the fungi is by utilizing medical plants that contain antifungal compounds. Cocoa leaves is a plants that has antifungal compounds such as caffeine, flavonoids and alkaloids. The aim of study was analyzing the effect of cocoa leaf extract on the growth of C. albicans and determining the optimal concentration of cocoa leaf extract in inhibiting the growth of C. albicans. The study used macerated cocoa leaf extract. The inhibitive testing method conducted by disc diffusion method. The concentrations of cocoa leaf extract were 25%, 50%, 75%, 100%, and nystatin was used as positive control and aquadest was negative control. All were possed on the disc and further incubated for 24 hours. The inhibition effect was measured by a caliper. Cocoa leaf extract can inhibit the growth of C. albicans, and the largest co-concentration in inhibiting C. albicans was 100%.